Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Terhadap Kualitas Laporan Keuangan Di Badan Amil Zakat Nasional Kota Bandung - Aris Munandar; Ateng Mulyadi (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
The potential of zakat in Indonesia is so great that it can become a financial solution to anticipate the problems of poverty and inequality in Indonesia. Likewise, the potential for zakat in the city of Bandung, which according to the calculations of experts can reach 2 trillion rupiahs per year, is very large to be managed professionally, but when viewed from the amount of existing zakat receipts it is only limited to 4.8 billion per year. So thus, the lack of income from zakat funds reflects the growing expectations of the public for the transparency or transparency and accountability of the management of zakat funds in the presence of financial reports. Therefore, the purpose of this study is to find out how much influence is given by financial accounting standards on the quality of financial reports at the National Amil Zakat Agency in the City of Bandung. The results of this study are that financial accounting standards significantly influence the quality of financial statements in the national amil zakat body.